(untitled) (Revista Internacional de Formação de Professores, 2022)
During the 1999 UNESCO World Conference on Higher Education, they were approved documents that emphasize the need of continuing and permanent education of university teachers and their pedagogical training. This article aims to describe the ongoing training of university teachers in the Catalan Autonomous Community, their evolution and their current state, taking the Training Plans of state universities as reference. The method applied is based on a qualitative approach, using the information provided by the documentary analysis of institutional references as a tool of information’s collection , as well as other documents of interest that contribute relevant information to the study. The most outstanding results obtained are that the permanent training of university teachers in Catalonia are located in a specific political and economic framework where teacher training has been redesigned and evolved to adapt to the current context. The fundamental results show there is a high concern of the Catalan institutions towards the improvement of the quality of university teaching, both at the direct or transversal disciplinary level and at the pedagogical level.